An innovative mobile application for construction programme managers - Fathi, Mohamad Syazli (2010)
Construction programme management is a complex and information-intensive environment. The construction programme management team requires access to construction information in real-time and when needed. The current increasing use of mobile devices offers an opportunity to meet this need. The efficient management of construction programmes is one of the major factors for improving stakeholders’ satisfaction. An innovative tool is needed in accessing the right information at the right time, especially when spontaneous and urgent decision-making is needed. To this end, the innovative use of a mobile device in delivering information and services to the management team in real-time and based on their current context offers significant benefits. This paper discusses context-aware computing, the enabling technologies for geolocation and the development of a prototype, mobile, context-aware application for construction programme management. The prototype system developed is based on the findings from an earlier study of user requirements which showed that the ability to provide relevant information and services at an appropriate time and at the most appropriate location has the potential to improve the monitoring and control of construction programmes. The prototype system demonstrates the provision of context-specific information and services to construction programme managers using a mobile device. The benefits and limitations of the proposed approach are discussed and conclusions drawn about the potential impact of enhanced information delivery for the efficiency of the construction programme managers.